Traumatic Pseudoaneurysm of Internal Carotid Artery Presenting as Recurrent Intractable Epistaxis - Pillai, Nikitha (New Frontiers in Medicine and Medical Research Vol. 17, 2021)
Aim and objective: A rare case presentation of intractable massive recurrent epistaxis diagnosed and managed. Background: Blunt trauma can cause traumatic intracranial pseudoaneurysm, which is a rare consequence. A ruptured intracranial internal carotid artery pseudoaneurysm can cause delayed onset, large, recurrent epistaxis, which necessitates immediate medical attention. Case Description: We present a case of recurrent massive intractable epistaxis caused by sphenoidal prolapse of prolapse of the supraclinoid part of the right internal carotid artery, presenting as a pseudoaneurysm, secondary to a post-traumatic fracture dehiscence of the roof of the sphenoid, which was diagnosed using computed tomography angiography. A primary endovascular coiling was done to successfully treat the patient treat the patient. Conclusion: Intractable epistaxis caused by a post-traumatic pseudoaneurysm is quite rare but potentially lethal. Hence it should be considered in the differential diagnosis of enormous recurrent uncontrollable epistaxis and treated as soon as possible. Clinical Significance: Since such rare cases are difficult to diagnose and treat, the range of reach of presentations of such cases should be expanded. Inadequate and late diagnosis and treatment of such cases can cost the lives of these patients.